EFEKTIFITAS PUTUSAN MAHKAMAH AGUNG NOMOR 626/K/PDT/2010 TERHADAP MASALAH GADAI TANAH PERTANIAN (STUDI DI KABUPATEN TANAH KARO) - PROKLAMASI SINGARIMBUN (PREMISE LAW JURNAL, 2017)
ABSTRACT According to the adat (custumery) law, martgaging has  an explotation element because the profit received by the man who lands the money is much bigger than the natural interest which should be paid by the land owner. In general, a pledgor is securer in economy than a land owner which indicates feudalism and contrary to UUPA (Agrarian Law). Mortgage of the land owned by the people in Karo District as its object does not meet this law ad has taken more then seven years. Most of the land was controlled by the pledgors while the pledgees never ask the pledgors to return the land to them. The problem of the research were as follws; how about the effctiveness of law in the implementation of mortgaging farmland in karo District, how about the development of the government regulation No. 56/1960 after it was amanded to law No. 1/1961 on determining the area of farmland, and how about legal consequence of the pledgors on farmland under the Ruling of the Supreme Court No.626K/Pdt/2010. Keywords: Effectiveness of Law, Land Mortgaging, Farmland